A facile deposition of large grain and phase pure α-FAPbI3 for perovskite solar cells via a flash crystallization. (September 2017) - Li, Ge; Zhang, Taiyang; Xu, Feng; Zhao, Yixin
Abstract: The α-HC(NH2 )2 PbI3 (FAPbI3 ) perovskite with narrower band gap and higher thermal stability is a promising candidate for high performance perovskite optoelectronic applications. However, it is difficult to achieve fast growth of a phase pure α-FAPbI3 perovskite because the unwanted δ-FAPbI3 usually first forms at lower temperature then converted into the wanted α-FAPbI3 at higher temperature. It takes long time annealing to complete the conversion of δ-FAPbI3 to α-FAPbI3, which could also lead to uncontrollable degradation of α-FAPbI3. Here we report a facile flash deposition of large grain phase pure α-FAPbI3 without any δ-FAPbI3 impurity by inhibiting the δ phase crystallization. In this method, a simple PMMA sealing to synchronize a flash α-crystallization process at appropriate temperature with the unwanted δ phase crystallization. Consequently, a high quality phase pure α-FAPbI3 with large grain size was fabricated into high performance perovskite solar cells. The strategy of flash crystallization would be a promising method for deposition of phase pure perovskite in future. Graphical abstract: Highlights: The difficult-to-make phase pure α-FAPbI3 perovskite with large grain was facilely fabricated. A flash crystallization help inhibited the unwanted formation of δ-FAPbI3 at lower temperature. The facile PMMA coating help realization of a flash crystallization of α-FAPbI3 at appropriate temperature.